Transformation Processes in Central and Eastern Europe: Liberalization, Integral Cultural Space and Social Environment for Economic Development - Melnikas, Borisas (Ekonomika, 2008)
The paper aims to evaluate the main features of the creation and development of an integral cultural and economic space in Europe, the main problems of economic and social development and provision of equal rights in the context of the transition processes in Central and Eastern Europe. Transformation processes in Central and Eastern Europe are described. The new challenges for economic development and social-oriented changes are analysed. In the paper, results of a research done over the recent several years into the diagnostics of the problems of transformations as well as economic and social development in Central and Eastern Europe are used, with a focus on the development of the integral space and human rights. The major findings show that the creation and development of an integral space in Europe is a very complex and controversial process implying various problems and conflicts. Therefore, to encourage the creation of an integral space in Europe, appropriate cultural policies should be implemented. These policies may embrace many priorities including the preservation of cultural diversity; adaptation and dissemination of integrated European dimensions; elimination of factors incompatible with humanism and democracy in all European countries; provision of equal rights to all groups of society. For implementing the key priorities of cultural policies, a number of pan-European special programmes are suggested. New non-traditional ideas regarding the possible economic and social development of Central and Eastern Europe are discussed.